(untitled) (Journal of Philosophy Culture and Political Science, 2024)
In today’s digitally interconnected world, social media has emerged as a prominent force shaping the behaviors, attitudes, and interactions of youth populations worldwide. This research endeavors to explore the intricate relationship between social media engagement and cybersecurity within the context of the Republic of Kazakhstan. The primary purpose of this scientific inquiry is to investigate the ways in which Kazakhstani youth engage with social media platforms and to assess the associated cybersecurity challenges and implications. Through a multidimensional approach, the study aims to delineate the main directions and ideas underlying the intersection of youth behavior on social media and the imperative of information security. This research holds significant scientific and practical importance by shedding light on the evolving dynamics of social media usage among Kazakhstani youth and the corresponding cybersecurity risks. By identifying key patterns, vulnerabilities, and protective measures, this study seeks to inform policymakers, educators, and stakeholders about the urgent need for comprehensive strategies to safeguard the digital well-being of young individuals. Employing a mixed-method research methodology comprising surveys, interviews, and data analysis, this study provides a comprehensive examination of social media dynamics and cybersecurity resilience among Kazakhstani youth. The main results and analysis reveal insights into the prevalent behaviors, perceptions, and attitudes of youth towards social media, alongside an assessment of cybersecurity vulnerabilities and mitigation strategies. The research underscores the importance of proactive measures to enhance cybersecurity awareness, digital literacy, and regulatory frameworks to address the emerging challenges posed by social media usage among Kazakhstani youth. By contributing empirical evidence and actionable insights, this study enriches the relevant field of knowledge and informs policy interventions aimed at fostering a safer and more secure digital environment for youth in Kazakhstan and beyond.